Common Pediatric Central Nervous System Tumors: Histology and Molecular Biology - Goussia, Anna C. (Journal of Pediatric Neuroradiology, 2016)
Central nervous system tumors represent the most common solid tumors of childhood. The heterogeneous group of gliomas comprises the majority of pediatric tumors while embryonal neoplasms represent the second most frequent group of tumors. Histopathological diagnosis according to World Health Organization is of great importance for defining prognosis and choosing the appropriate treatment. Recently, attempts have been made to correlate specific genomic alterations to clinical outcome. Adding molecular information to classic histology seems to improve diagnostic accuracy and risk stratification of patients.
Keywords: gliomas; medulloblastoma; pediatric; histology; molecular biology